2016
DOI: 10.1515/pjvs-2016-0085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High-field and Low-field Magnetic Resonance Imaging of Stifle Joint Disorders in Dogs

Abstract: The most common cause of hindlimb lameness in dogs is cranial cruciate ligament rupture. In 48-77.3% of the population this trauma leads to secondary damage of the meniscus. Depending on the magnetic strength of the used device, different diagnostic accuracy can be achieved. The examination sensitivity of magnetic resonance imaging is affected by many factors which are independent of diagnostic strength, such as correct positioning of the patient, size of the stifle joint examined, or selection of the right pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(124 reference statements)
0
4
0
1
Order By: Relevance
“…Among the currently available diagnostic imaging techniques, MRI can provide the greatest range of information and the finest accuracy in detecting subtle abnormalities due to the highest soft tissue contrasts [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Conventional MRI studies are conducted at functional rest, but some spinal or orthopedical diseases, characterized by articular instability and a dynamic component, can be underestimated when imaged in these conditions [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the currently available diagnostic imaging techniques, MRI can provide the greatest range of information and the finest accuracy in detecting subtle abnormalities due to the highest soft tissue contrasts [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Conventional MRI studies are conducted at functional rest, but some spinal or orthopedical diseases, characterized by articular instability and a dynamic component, can be underestimated when imaged in these conditions [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging is an excellent advanced imaging tool for the study of both orthopedic [ 3 , 4 , 5 ] and neurological diseases [ 6 , 7 ]. Due to its high soft tissue contrast, musculoskeletal structures (i.e., tendons, ligaments, fascial and synovial membranes), nervous structures, blood vessels, and osseous tissues can be clearly assessed and evaluated for pathological changes [ 3 , 4 , 5 , 6 , 7 , 8 ]. Conventional MRI studies are usually performed at functional rest.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that both systems are reliable in diagnosing meniscal tears and ruptures of the anterior cruciate ligament (Kladny et al ). Similarly in dogs, high‐ and low‐field MRI allowed for early detection of osteoarthritis, cranial cruciate ligament and subchondral bone or bone marrow lesions (Przeworski et al ). Similar to other advanced imaging modalities of the stifle (Crijns et al ; Judy ), general anaesthesia for MRI is required to eliminate rocking motion of the proximal limb that would occur during standing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of the accessory metacarpal ligaments and the associated soft tissue trauma are caused by hyperextension subluxation injuries and can be identified on MRI. This imaging modality can also detect joint effusion, peritendinous fluid accumulation, foreign bodies, and osteomyelitis (1,29,31). MRI is typically performed in several different acquisition sequences that emphasise different magnetic properties of tissues; commonly T1-and T2weighted and proton density (PD) properties are illustrated.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%